Nove tehnike smučanja - nove poškodbe? Analiza smučarskih poškodb v letih 2004 in 2005 - Veselko, Matjaž (Zdravniški vestnik, 2008)
New developments in ski technology have influenced the rate and structure of'ski injuries in the past. Lately, skies and snowboards with carved steel edges have taken over traditionally shaped skies and introduced a new, so called carving technique. In this paper we analysed ski injuries treated at Department of Traumatology during 2004 and 2005, to see whether new equipment and skiing techniques have changed injury rate andpattern. The rate of ski injuries has not changed importantly while thepattern is quite different. The number of high velocity and high energy injuries has raised, leading to highernumber of head, trunk and multiple injuries. Number of upper extremity injuries has raised predominantly due to snowboarding. Carved edges and carving led to some new tipical mechanisms of injuries to the knee and upper tibia. New design of skies and snowboards with carved edges have changed skiing technique. The velocity ofskiers has raised, ski-tracking is defined byradius of ski edges and decreased abillity to decelerate or to change direction in carving have led to new injury patterns. New mechanisms of injuries dictate changes of security measures such as new release systems of ski bindings, protection braces, skiing technique improvements and improved resort management and safety.
Keywords: poškodbe; Rane in poškodbe; Skiing; Smučanje; Wounds And Injuries